Search 75,466 tutors
FIND TUTORS
Ask a question
0 0

Combine the rational expressions

Tutors, please sign in to answer this question.

1 Answer

                 2                         4                       3    
... =  ———————  –  ———————  +  ———————  =  
         (x + 2)(x + 3)       (x + 1)(x + 3)        (x + 1)(x + 2)
    
 x ≠ -3 , x ≠ -2 , x ≠ -1  LCD = (x + 1)(x + 2)(x + 3) 
    
            2(x + 1)                          4(x + 2)                       3(x + 3)  
=  ——————————  –  ——————————  +  ——————————  =
    (x + 1)(x + 2)(x + 3)        (x + 1)(x + 2)(x + 3)      (x + 1)(x + 2)(x + 3)  

    2x + 2 - 4x - 8 + 3x + 9                    x + 3
= ————————————  =  ———————————  = 
     (x + 1)(x + 2)(x + 3)            (x + 1)(x + 2)(x + 3)  

             1                          1  
=  ———————  =  ——————— 
     (x + 1)(x + 2)         x2 + 3x + 2